Bank capital regulation in a zero interest environment - Robin Döttling (European Central Bank (ECB), 2020)
How do near-zero interest rates affect optimal bank capital regulation and risk-taking? I study this question in a dynamic model, in which forward-looking banks compete imperfectly for deposit funding, but households do not accept negative deposit rates. When deposit rates are constrained by the zero lower bound (ZLB), tight capital requirements disproportionately hurt franchise values and become less effective in curbing excessive risk-taking. As a result, optimal dynamic capital requirements vary with the level of interest rates if the ZLB binds occasionally. Higher in ation and unconventional monetary policy can alleviate the problem, though their overall welfare effects are ambiguous.
Keywords: G21; G28; E44; E58; 330; Zero lower bound; search for yield; capital regulation; franchise value; unconventional monetary policy